Faktor-faktor yang mempengaruhi audit delay pada perusahaan Badan Usaha Milik Negara (BUMN) yang terdaftar di Bursa Efek Indonesia - Michella Beauty Irfania Rerungan; Herman Karamoy; Steven Josia Tangkuman (Manajemen Bisnis dan Keuangan Korporat, 2026)
Indonesian State-Owned Enterprises (SOEs) are required to maintain a high level of transparency and accountability, particularly in the timeliness of audited financial reporting. However, audit delay remains a persistent issue among SOEs listed on the Indonesia Stock Exchange (IDX). This study examines the effects of independent commissioners, board size, operational complexity, debt ratio, and audit opinion on audit delay. Using a quantitative approach, this study analyses 65 firm-year observations from 13 SOEs over the period 2020–2024, employing multiple linear regression analysis. The results indicate that board size has a significant negative effect on audit delay, while operational complexity and debt ratio have significant positive effects. In contrast, independent commissioners and audit opinion do not significantly affect audit delay. These findings suggest that internal managerial capacity and organizational complexity play a more critical role than formal governance structures in determining audit timeliness. This study contributes to the audit timeliness literature by providing empirical evidence from state-owned enterprises in an emerging market context.